Protective effects of 4-HBd on blood–brain barrier integrity in MCAO/R model rats based on brain pharmacokinetic characteristics - Feng, Jin; Yang, Qian; Chen, Ming; Wang, Yan; Luo, Dan; Hu, Dongxiong; Cheng, Jianjun; Song, Xuelan; Zhou, Xiaonan; Meng, Qingting; Lin, Qing; He, Fangyan (Frontiers in Pharmacology, 2025)
ObjectivesThis study explored the brain-targeting properties and mechanisms of 4-hydroxybenzaldehyde (4-HBd), the primary active component of Gastrodia elata, in mitigating ischemic stroke (IS)-induced injury by preserving blood–brain barrier (BBB) integrity, based on brain pharmacokinetic characteristics.MethodsThe anti-IS effects of the G. elata extract were assessed using a rat middle cerebral artery occlusion/reperfusion (MCAO/R) model, leading to the identification of 4-HBd as the principal active ingredient. BBB protection was evaluated through neurological scoring, Evans Blue (EB) extravasation, cerebral infarct volume, and ultrastructural integrity. Oxidative stress markers, including superoxide dismutase (SOD), malondialdehyde (MDA), nitric oxide (NO), and inducible nitric oxide synthase (iNOS), were quantified in ischemic brain tissue via biochemical assays. The expression levels of tight junction (TJ) proteins claudin-5 and occludin, as well as matrix metalloproteinase MMP-2/9 and aquaporin-4 (AQP-4), were analyzed by Western blotting. Microdialysis, combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS), was employed to determine the temporal distribution of 4-HBd in the brains of both normal and MCAO/R model rats. The ability of 4-HBd to scavenge intracellular reactive oxygen species (ROS) in brain endothelial cells (bEnd.3) was evaluated using a single-cell biochemical analyzer.ResultsG. elata ethanol extract exhibited significant anti-IS effects. When compared with the model group, 4-HBd treatment markedly alleviated BBB disruption and neurological deficits, suppressed oxidative stress in ischemic brain tissue, reduced MDA and NO levels, and enhanced SOD activity. The expressions of claudin-5, occludin, MMP-2/9, and AQP-4 were significantly upregulated in the 4-HBd group relative to the model group. Additionally, 4-HBd selectively eliminated nuclear-derived ROS. Pharmacokinetic analysis demonstrated that 4-HBd preferentially accumulated in the striatum and cortex of both normal and MCAO/R model rats. Under ischemic conditions, 4-HBd exhibited accelerated cortical penetration, increased exposure, and prolonged retention.ConclusionThese findings indicate that 4-HBd exerts a pronounced brain-targeting effect and preserves BBB integrity via the RNS/ROS-MMP-TJ signaling pathway, highlighting its potential as a therapeutic agent for IS.